Tax Avoidance and the Implications of Weak Internal Controls - Bauer, Andrew M. (Contemporary Accounting Research, 2016)
Abstract I examine whether corporate tax avoidance is associated with internal control weaknesses ( ICW s) disclosed under the Sarbanes‐Oxley Act ( SOX ). ICW s disclosed under SOX are frequently related to a firm's tax function. When pervasive ICW s exist, the likelihood increases that these frequent tax‐related ICW s spill over from financial reporting issues to tax avoidance objectives. Thus, my research helps corporate stakeholders understand the implications of internal controls beyond simply financial reporting objectives. Results indicate that, on average, firms with a tax‐related ICW have a 4 percent higher three‐year cash effective tax rate relative to firms without any such weaknesses. Further estimates reveal that this negative relation stems from pervasive, company‐level tax ICW s. Analysis of remediation suggests a causal link. I find that after remediating tax‐related ICW s, firms report higher levels of tax avoidance in the future. Broadly, these findings support that internal control quality represents a proxy for internal governance, and thus the strength of alignment between managers and shareholders. Furthermore, tax‐related internal controls represent an important underlying determinant of tax avoidance with significant cash flow effects, and implications beyond financial reporting.